2018
DOI: 10.3389/fpsyg.2018.00754
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Nature Exposure and Outdoor Activities Associated With Occupational Well-Being Among Employees

Abstract: This research addresses the profiles of nature exposure and outdoor activities in nature among Finnish employees (N = 783). The profiles were formed on the bases of nature exposure at work and the frequency and type of outdoor activities in nature engaged in during leisure time. The profiles were investigated in relation to work engagement and burnout. The latent profile analysis identified a five-class solution as the best model: High exposure (8%), Versatile exposure (22%), Unilateral exposure (38%), Average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 51 publications
2
37
0
Order By: Relevance
“…However, our results indicated that participants in Experiment 2 were attentive to the environment. This "variety is the spice of life" explanation is not consistent with research showing that more time spent in nature is linked to greater positive affect [an effect partially accounted for by the quality of the nature experience (i.e., fascination; Sato and Connor, 2013)] and that increased exposure or availability of natural environments is related to many benefits, such as better mental health (Alcock et al, 2014), less stress, depression, and anxiety (Thompson et al, 2012;Beyer et al, 2014), and greater occupational well-being (Hyvönen et al, 2018). Future research should investigate the possibility that with repeated exposure, each individual exposure results in smaller immediate affective benefits due to hedonic adaptation, but that greater cumulative exposure results in larger long-term affective benefits.…”
Section: Discussionmentioning
confidence: 80%
“…However, our results indicated that participants in Experiment 2 were attentive to the environment. This "variety is the spice of life" explanation is not consistent with research showing that more time spent in nature is linked to greater positive affect [an effect partially accounted for by the quality of the nature experience (i.e., fascination; Sato and Connor, 2013)] and that increased exposure or availability of natural environments is related to many benefits, such as better mental health (Alcock et al, 2014), less stress, depression, and anxiety (Thompson et al, 2012;Beyer et al, 2014), and greater occupational well-being (Hyvönen et al, 2018). Future research should investigate the possibility that with repeated exposure, each individual exposure results in smaller immediate affective benefits due to hedonic adaptation, but that greater cumulative exposure results in larger long-term affective benefits.…”
Section: Discussionmentioning
confidence: 80%
“…Opportunities to interact with nature across seasons and at all times of the day and a range of human–nature relationships must be encouraged (Barnes et al., 2019; Fabjanski & Brymer, 2017; Richardson & McEwen, 2019). Exercising outdoors and in sight of nature has additional benefits for our relationship with the natural world by reducing anxiety (Bratman et al., 2015; Hyvönen et al., 2018; Lawton et al., 2017; Niedermeier, Hartl, & Kopp, 2017; Wooller, Barton, Gladwell, & Micklewright, 2016). Even virtual reality interactions can have a positive impact for those with limited access to nature (Calogiuri et al., 2018; Nguyen & Brymer, 2018).…”
Section: Urban Ecosystems In the Global Biodiversity Crisis And In Edmentioning
confidence: 99%
“…We must provide environments that in themselves are compelling and encourage time spent in nature. Exercising outdoors and in sight of nature has additional benefits of the relationship with the natural world and reducing anxiety (Hyvönen et al., 2018; Lawton et al., 2017; Niedermeier et al., 2017; Wooller et al., 2016). Even virtual reality interactions can have a positive impact for those with limited access to nature (Calogiuri et al., 2018; Nguyen & Brymer, 2018).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Ulrich (1984) verified that being exposed to nature has a measurable effect in the recovery process of persons after surgery. Nature exposure has had positive effects on work environments and the personal affiliated with them (Hyvönen et al, 2018). Grinde and Grindal Patil (2009) denominated Biophilia to the regard for plants and living creatures developed by humans along history and across cultures.…”
Section: A Note On Therapy In the Outdoors -Nature As A Moving Bodymentioning
confidence: 99%